Single-Nucleus RNA Sequencing Reveals the Transcriptome Profiling of Ovarian Cells in Adolescent Cyprinus carpio - Mingxi Hou; Jin Zhang; Qi Wang; Ran Zhao; Yiming Cao; Yingjie Chen; Kaikuo Wang; Ning Ding; Yingjie Qi; Xiaoqing Sun; Yan Zhang; Jiongtang Li (Animals)
The common carp (Cyprinus carpio) is a crucial freshwater species cultivated worldwide for food consumption. Female carp have better growth performance than males, which fascinates scholars to uncover the mechanism of gonadal differentiation and produce mono-sex populations. However, the mechanism of ovarian development at single-cell resolution is limited. Here, we conducted single-nucleus RNA sequencing in adolescent common carp ovaries. Our study obtained transcriptional profiles of 13,155 nuclei and revealed 13 distinct cell clusters in the ovaries, including three subtypes of germ cells and four subtypes of granulosa cells. We subsequently performed pseudotime trajectory analysis to delineate potential mechanisms underlying the development of germ cells and granulosa cells. We identified 1250 dynamic expression genes in germ cells and 1815 in granulosa cells (q-value < 0.01), including zp3, eif4a2 and aspm in germ cells and fshr and esr1 in granulosa cells. The functional annotation showed that dynamic expression genes in germ cells were involved in sperm–egg recognition and some terms related to meiosis, such as sister chromatid segregation and homologous recombination. Genes expressed dynamically in granulosa cells were related to the TGF-β signaling pathway, response to gonadotropin, and development of primary female sexual characteristics. In addition, the dynamic genes expressed in granulosa cells might relate to the complex communication between different cell types. In summary, our study provided a transcriptome profile of common carp ovaries at single-nucleus resolution, and we further revealed the potential cell type-specific mechanisms underlying oogenesis and the differentiation of granulosa cells, which will facilitate breeding all-female common carp populations.